Differentiation Theory and the Global South as a Metageography of International Relations (2018)
In this article, I argue that while the Global South has replaced the Third World as the prevalent term for describing structural global inequalities in International Relations, little research is directed at its theoretical implications. I discuss the conceptual evolution of the term from the Third World narrative, interpreting the literature as an implicit rejection of myopic ontologies relying on economic, cultural, or political hierarchies. I then suggest connecting the terminology to the theory of functional differentiation. By avoiding forms inherited from classical social theory, the Global South can be conceptualized in a more productive way that is better attuned to contemporary theoretical discussions. © The Author(s) 2018.